Study guides

Q: How do I simplify the expression -10 plus 6(4t-8)?

Write your answer...

Submit

Related questions

In the expression '15b + 23b + 10', the coefficients are 15, 23, and 10.If you simplify the expression to '38b + 10", then the coefficients are 38 and 10.

5/ 2 -4/ 5 plus 2 expression can be written in simple form as 37/10.

10 square root 3.

-15

-12 + 6 - 10 - 6 +15 = -7

86

answer=3k-3

It is an algebraic expression in the form of: 8x+10

15 + 10 - 13 - 5 = 7

Expression: x+10+5x Solve: x+5x=6x Answer: 6x+10

1/3 + 3/5 + 7/10 = 49/30 or 119/30

There is no need to simplify this, it is only a sum. 21 + (10/2) - 18 = 8

3 + 92 = 95

It is simply 5x + 10. Since it is an expression, there can be no solution.

There is no equation in the question, only an expression. An expression cannot have a solution.

5 plus 8

It is: 4k-10+7-7k combines to -3k-3

-16

5+8 is the same as 10+3 = 13

0+10

10

Unless you have a value for 'h', the answer will just be an expression: 10 + 7h

simplify the square foor of 49 times x to the third time y to the sixth times the absolute value of z squared

It is simply: 10+q

x2 + 7x + 10 = (x + 2)(x + 5)